Computed tomography images to assess the dose in irradiated chestnut fruits - Antonio, Amilcar L. (2013)
Report of the Methyl Bromide Technical Options Committee. United Nations Environment Programme. EU, 2008. Commission Decision. Official Journal of the European Union, L 258/68, 26 September. Antonio, A. L., Carocho, M. Bento, A., Quintana, B., Botelho, M.L., Ferreira, I.C.F.R. (2012). Effects of gamma radiation on the biological, physico-chemical, nutritional and antioxidant parameters of chestnuts - A review. Food and Chemical Toxicology 50 (9), pp. 3234-3242.